2018
DOI: 10.4103/0366-6999.245269
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection is Associated with Occurrence of Proteinuria in Type 2 Diabetes Patients

Abstract: Background:Type 2 diabetes (T2DM) patients are susceptible to Helicobacter pylori (HP), and it has been reported that the occurrence of proteinuria is associated with HP infection in T2DM patients; however, this view remains controversial. This meta-analysis aimed to explore the association between HP infection and the occurrence of proteinuria in T2DM patients. In addition, we hope to provide some recommendations to readers in clinical or related fields.Methods:Our meta-analysis was conducted with the methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Epidemiological surveys have indicated that the possible pathological consequences of HP infection are not restricted to the gastroduodenal tract [ 15 , 16 , 17 ]. Helicobacter gastritis is correlated with a wide range of extradigestive diseases, such as heart, vessel, skin, endocrine, respiratory, hematopoietic, immune, and central nervous system conditions [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological surveys have indicated that the possible pathological consequences of HP infection are not restricted to the gastroduodenal tract [ 15 , 16 , 17 ]. Helicobacter gastritis is correlated with a wide range of extradigestive diseases, such as heart, vessel, skin, endocrine, respiratory, hematopoietic, immune, and central nervous system conditions [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among 47 studies analyzed, they found a lower prevalence of H pylori in patients with CKD versus controls (OR 0.64; CI 95%: 0.52‐0.79) and this result was also confirmed by a meta‐regression analysis . Shi et al, in another meta‐analysis on the association between H pylori infection and proteinuria among patients with T2DM, reported that infected diabetic patients have twice as high a risk of proteinuria as uninfected patients (OR 2.0; CI 95%: 1.48‐2.69) …”
Section: Kidney Diseasesmentioning
confidence: 75%
“…Another meta-analysis [41] showed that Type 2 diabetes (T 2 DM) patients with Hp infection had a 2 times higher risk of the occurrence of proteinuria than patients without Hp infection, indicating that Hp infection was associated with the occurrence of proteinuria in T 2 DM patients. Hp radical surgery might be a therapeutic option for protecting renal function in patients with T 2 DM [42]. However, a cross-sectional study [43] investigating the association between Hp infection and chronic kidney disease (CKD) did not find any significant difference in the prevalence of proteinuria and the overall CKD between the Hp infection group and non-infection group.…”
Section: Discussionmentioning
confidence: 96%